The Influence of Organizational Culture and Leadership to Organizational Commitment and its Implication to Work Engagement of Civil Servant in Riau Islands Province - Amril Ghaffar Sunny; Fais bin Ahmad; Haslinda Hasan, (International Journal of Management Studies (IJMS), 2021)
Focus of this research is the influence of organizational culture and leadership to organizational commitment and its implication to work engagement of civil servant in Riau Islands Province. In general, this study aims to review, assess, and recognize how the influence of organizational culture and leadership of Civil Servant Organization which is Civil Servant in Indonesia in according to enhance organizational commitment and work engagement because based on the result of previous research is considered still not able to achieve the objectives proclaimed in the Act of the Republic of Indonesia Number 43 of 1999 regarding the Principles of Civil Servant, while Civil Servant is a principal element of government executor. This study has been studied using quantitative research methods. The result of the research shows that there is influence of organizational culture and leadership to organizational commitment and there is also an implication to work engagement. Therefore, if the work engagement of employees wants to be improved then it needs to get more attention to the elements of organizational culture, leadership, and organizational commitment.